Preparation of A Poly (Vinylalcohol) (PVA)/Peat/Organoclay /Kno3 Composite Bead as Biofilter Material for Biofiltration of Volatile Organic Compounds - Chan, Wu-Chung; Guo, Hong-Siou (The International Journal of Biotechnology, 2014)
In this study, a PVA/peat/organoclay/KNO3 spherical composite bead was prepared and was proved suitable as a biofilter material. This composite bead was a porous spherical particle with a diameter of 3.0-5.0 mm, a density of 1.23 g/cm3 and a porosity of about 50%. The organoclay was prepared by hexadecyl trimethyl ammonium bromide (HDTMA) exchanged clay. The biochemical kinetic behaviors of n-butyl acetate in the spherical PVA/peat/HDTMA-clay/KNO3 composite bead biofilter (Clay biofilter) and PVA/peat/granular activated carbon (GAC)/ KNO3 spherical composite bead biofilter (GAC biofilter) were investigated. The values of half-saturation constant Ks for Clay biofilter and GAC biofilter were 69.86 and 38.49 ppm, respectively. The values of maximum reaction rate Vm for Clay biofilter and GAC biofilter were 23.77 and 22.97 ppm/s, respectively. Diffusion-limited Zero-order kinetic was regarded as the most adequate biochemical reaction model. The microbial growth rate kg and biochemical reaction rate kd for two biofilters were inhibited at higher inlet concentration. The degree of inhibitive effect was more pronounced in the GAC biofilter in microbial growth process and that was almost the same in two biofilters in the biochemical reaction process. The maximum elimination capacity for Clay biofilter and GAC biofilter was 139.10 and 154.67 g-C/h-m3 bed volume, respectively. The PVA/peat/HDTMA-clay/KNO3 composite bead was suitable as a biofilter material.